Sistem Antrian Pasien pada Praktek Dokter menggunakan Algoritma FCFS Dan Notifikasi SMS Berbasis Web - Hendrawaty, Muhammad Arhami, Muhammad Iqbal (Jurnal Elektro dan Informatika, 2021)
Queue is an important thing to discuss as part of testing one's patience, so it can be said that the queue has become a part of everyday life for everyone. From these problems, with a queuing system that implements FCFS and WEB-based methods. To make it easier for patients to queue, the FCFS algorithm is relatively easy to use because it is the simplest and more efficient scheduling algorithm when used for queuing at the doctor's practice so that the first patient to queue is to be served. Notification feature in the form of SMS provided by the system so that patients get a notification when the patient's queue number is near and the schedule update if there is a patient has already taken a card and cannot be present.